ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA KOMUNIKASI DAN INFORMASI DALAM HUMAS MIS AL-JIHAD KOTA PALANGKA RAYA - Malik Kurnia Ali; Nurul Hikmah; Syahmidi Syahmidi (STKIP Pesisir Selatan, 2026)
The development of the digital era and information technology has brought significant changes to the advancement of science, technology, and the arts, particularly in the transformation of information into knowledge that can be widely accessed without limitations of space and time. This condition encourages educational institutions to utilize social media as an effective means of communication and information dissemination, as institutions that fail to adopt technology appropriately may fall behind. This study aims to analyze the use of social media by the public relations unit of MIS Al-Jihad, Palangka Raya City, as a communication and information medium for parents and the wider community. This research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The informants in this study consisted of the Vice Principal for Public Relations, public relations staff, and students’ parents. The results indicate that the public relations unit of MIS Al-Jihad has optimally utilized social media as a communication and information medium, as evidenced by the rapid, transparent, and easily accessible dissemination of school information, as well as positive responses from parents and the community. Social media is used to convey various types of information, such as school activities, examinations, and new student admissions. The use of social media plays an important role in enhancing information transparency, strengthening two-way communication, and building trust and a positive image of the madrasah amid rapid digital technological developments.